Negotiating Knowledge in Early Modern Empires
XIV, 273 p. 1 illus.
Keywords: This volume takes a decentered look at early modern empires and rejects the center/periphery divide. With an unconventional geographical set of cases, including the Holy Roman Empire, the Habsburg, Iberian, French and British empires, as well as China, contributors seize the spatial dynamics of the scientific enterprise.